LICHENOCHEMICAL STUDY OF THE LICHEN HYPOTRACHYNA CIRRHATA - Castro Mandujano, Nino (2023)
Peru is one of the most diverse countries in the world, since it contains innumerable natural resources, this is due to a great variety of ecosystems that make it conducive to the development of certain species, including lichens; For this reason, it is our interest to study lichens chemically (lichenochemistry). In the present work, the lichen Hypotrachyna cirrhata, collected in the district of Churín-Lima-Peru, was studied. Successive extractions were made with methanol from 150 g of previously conditioned sample; the separation and purification processes were carried out using classical chromatographic techniques such as Sephadex LH-20, column chromatography, thin layer chromatography in order to obtain the pure secondary metabolites, and finally, to elucidate their chemical structures by 1H-NMR. In this investigation, from the methanolic extract of the lichen Hypotrachyna cirrhata, the following compounds were elucidated: protoliquesterinic acid, ergosterol peroxide and 2,4-dihydroxy-3-hydroxymethyl-6-methylbenzaldehyde